Traditional plant use during lactation and postpartum recovery: Infant development and maternal health roles. (28th October 2021) - Sibeko, Lindiwe; Johns, Timothy; Cordeiro, Lorraine S.
Abstract: Ethnopharmacological relevance: Evidence of phytochemical roles in infant development and maternal recovery offers insights into beneficial functions of traditional plant use during lactation and the postpartum period. Ethnopharmacological research has relevance to global priorities on maternal and child health, to understanding origins and determinants of human self-medication, and for reconciling traditional postpartum practices and mainstream healthcare. Aim of the study: Present emerging evidence, within evolutionary and socio-cultural contexts, on the role of maternal consumption on transfer of phytochemicals into breast milk with impacts on maternal and child health, and on infant development. Establish current state of knowledge and an ethnopharmacological research agenda that is attentive to cross-cultural and regional differences in postpartum plant use. Materials and methods: An extensive literature review using Medline, Scopus, and Web of Science focused on traditional and contemporary use and socio-cultural context, as well as physiological, pharmacological, toxicological, and behavioral activities of plants used medicinally by women during postpartum recovery and lactation. Results: The most widely reported postpartum plants show antimicrobial, anti-inflammatory, immunological, and neurophysiological activities, with low toxicity. Phytochemicals transfer from maternal consumption into breast milk in physiological concentrations, while animal studies demonstrate immunomodulation and other actions of medicinal plants during lactation. Reporting on the use and diverse traditional knowledge of women about plants during the postpartum period is obscured by the marginal place of obstetric issues and by gender biases in ethnobotanical research. In many contemporary contexts use is prejudiced by precautionary risk warnings in health literature and practice that confound lactation with pregnancy. Conclusions: Although systematic investigation of postpartum plant use is lacking, known pharmacological activities support potential benefits on infant development and maternal health with immediate and long-term consequences in relation to allergic, inflammatory, autoimmune, and other diseases. An ethnopharmacological agenda focused on the perinatal period requires directed methodologies and a regional approach in relation to culturally-specific knowledge and practices, traditional plant use, and local health needs. Testing the hypothesis that phytochemicals transferred from medicinal plants into breast milk impact the human immune system and other aspects of infant development requires extended analysis of phytochemicals in human milk and infant lumen and plasma, as well as effects on gastrointestinal and milk microbiome. Graphical abstract: Image 1 Highlights: Integrated socio-cultural, ecological, behavioral, physiological and phytochemical overview. Perinatal self-medication and a supporting role of women elders key in origins of medicine. Phytochemicals transferred to breastmilk have potential impacts on immune system and other aspects of neonatal development. Maternal benefits for physical recovery and disease protection, breastfeeding success, and emotional equilibrium. Ethnopharmacological research agenda delineated with interconnected traditional botanical knowledge and analytical streams.